2017
DOI: 10.21037/jovs.2017.06.10
|View full text |Cite
|
Sign up to set email alerts
|

Materials and techniques in chest wall reconstruction: a review

Abstract: Extensive chest wall resection and reconstruction are a challenging procedure that requires a multidisciplinary approach, including input from thoracic surgeon, plastic surgeon and oncologist. In particular chest wall neoplastic pathology is associated with high surgical morbidity and can result in full thickness defects hard to reconstruct. The goals of a successful chest wall reconstruction are to restore the chest wall rigidity, preserve pulmonary mechanic and protect the intrathoracic organs minimizing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
149
0
16

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(166 citation statements)
references
References 57 publications
1
149
0
16
Order By: Relevance
“…The flaps utilized were probably still the most commonly used. 6,7 Low-recurrence rates, less complication, and better survival rates demonstrated in our series could be attributed to wide oncological reconstruction of the tumors as well as appropriate methods in wound closure. All our resection margins were negative with the nearest being 1.5 cm from the Management of Extensive Dermato-fibro-sarcomas Nangole tumor margins.…”
Section: Discussionmentioning
confidence: 54%
“…The flaps utilized were probably still the most commonly used. 6,7 Low-recurrence rates, less complication, and better survival rates demonstrated in our series could be attributed to wide oncological reconstruction of the tumors as well as appropriate methods in wound closure. All our resection margins were negative with the nearest being 1.5 cm from the Management of Extensive Dermato-fibro-sarcomas Nangole tumor margins.…”
Section: Discussionmentioning
confidence: 54%
“…Bone grafts have the advantage of being able to incorporate with revascularization and cellular repopulation, causing an increased resistance to infection. 14 Although all reported cases have produced positive outcomes, the literature regarding the use of bone grafts in sternal defects is limited. Nahabedian et al 8 reported a case in which a 7-cm sternal defect secondary to cardiac transplantation was reconstructed using fibular allograft.…”
Section: Discussionmentioning
confidence: 99%
“…The cellular exposure and repopulation process are better regulated, thereby reducing risk of rejection. 15 Finally, we utilized well-vascularized soft tissue coverage to prevent exposure of our prosthesis and minimize the risk of infection. 1,[16][17][18] During preparation, the MMA is mixed to a gel-like consistency and subsequent polymerization takes 5 to 10 minutes during which the prosthesis is shaped (Lardinois et al 5 ).…”
Section: Discussionmentioning
confidence: 99%